The complete mitochondrial genome sequence of Rhynchoconger ectenurus (Anguilliformes: Congridae) - Wei Shi; Hui Yu (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitochondrial genome of Rhynchoconger ectenurus was sequenced by high-throughput sequencing method. The length of this genome is 17,716 bp, containing 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and 2 large non-coding regions. ND6 and 8 tRNA genes are encoded by L-strand, and others are encoded by H-strand. Phylogenetic tree based on 13 protein-coding genes shows that the clade of Rhynchoconger ectenurus is closely clustered with that of Conger japonicus, and families Anguillidae and Synaphobranchidae have the closer relationship to Congridae, compared to Muraenidae.